2021
DOI: 10.5935/1984-0063.20200110
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Valerian on sleep spindles in a model of neuropathic pain

Abstract: Introduction:Valeriana officinalis is known to be one of the most famous herbal supplements for the treatment of anxiety and insomnia. Despite its widespread use in most countries all around the world, there is little scientific information and research on how this medication affects sleep patterns, and there are almost no studies on its effects on the characteristics of sleep spindles. Material and Methods: The present study was conducted to investigate the effects of Valerian extract (VAL) on sleep spindles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Chemical structures of melatonin and valerenic acid Currently, studies with valerian focused on treating anxiety and insomnia continue to advance with very positive results (Das et al, 2021;Borrás et al, 2021). Also, in trials in patients with neuropathies (Soltani et al, 2021), mental disorders such as Alzheimer's (Marde et al, 2022), and in pregnancy (Kennedy et al, 2013), the beneficial effects of valerian extracts, as well as other phytotherapeutics, have been proven with interesting results. Another attractive line of research with valerian is the studies against skeletal muscle atrophy, of great interest in athletes (Kim et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Chemical structures of melatonin and valerenic acid Currently, studies with valerian focused on treating anxiety and insomnia continue to advance with very positive results (Das et al, 2021;Borrás et al, 2021). Also, in trials in patients with neuropathies (Soltani et al, 2021), mental disorders such as Alzheimer's (Marde et al, 2022), and in pregnancy (Kennedy et al, 2013), the beneficial effects of valerian extracts, as well as other phytotherapeutics, have been proven with interesting results. Another attractive line of research with valerian is the studies against skeletal muscle atrophy, of great interest in athletes (Kim et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that oral administration of V. officinalis dry root or rhizome to mice increased gamma-aminobutyric acid type A receptor subunit beta3 (GABRB3), the gene that encodes the GABA A receptor β 3 subunit, gene mRNA expression (Mulyawan et al, 2020b). The oral administration of V. officinalis hydroalcoholic extract suffering from neuropathic pain decreased REM sleep, increased NREM sleep, the density and frequency of sleep spindle, as well as sleep quality (Soltani et al, 2021).…”
Section: In Vitro/in Vivomentioning
confidence: 99%